A preliminary study for image degradation by grid cutoff and radiation scattering in oblique X-ray imaging - Kim, Young Beom; Kim, Gyoung-Hee; Kim, Yong-Gwon (Multimedia tools and applications, 2024)
In clinical X-ray imaging, a focused grid is used to enhance image contrast by removing scattered radiation. The focused grid removes scattered radiation only when the X-ray source is located in the focal point of the grid. In oblique imaging, the grid cuts off some of the primary radiation because the X-ray radiation is not aligned with the lead strips. If the tilting angle of the grid elements and the direction of X-ray radiation are not aligned, it results in less X-ray reaching the imaging detector. Therefore, in oblique imaging cases, the exposure condition is generally increased to obtain a clinically valuable image. In this paper, we propose a method to acquire proper image quality in terms of both contrast and signal-to-noise ratio (SNR) in oblique X-ray imaging by positioning the subject in a specific grid region where the X-ray projection is aligned with the tilted angle of the grid lead strips. We examined experimental imaging with several types of radiographic phantoms, and the results demonstrate the feasibility of the proposed method. This study is applicable to non-standard X-ray imaging cases involving patients who are difficult to position correctly in oblique views. In such cases, the proposed approach sets the direction of X-ray radiation without requiring patient movement.